Cross‐reactive humoral responses to influenza and their implications for a universal vaccine. (13th February 2013) - Chiu, Christopher; Wrammert, Jens; Li, Gui‐Mei; McCausland, Megan; Wilson, Patrick C.; Ahmed, Rafi
Abstract : Influenza remains one of the most important causes of respiratory infection despite the widespread availability of vaccines. As effective vaccines against influenza principally rely on the induction of strain‐specific neutralizing antibodies for their protective efficacy, drifted escape mutants and genetically reassortant pandemic strains can rapidly overcome them. Several groups have recently described cross‐reactive influenza antibodies in humans, some of which bind to the conserved hemagglutinin stem. If such antibodies could be consistently induced at high levels by vaccines, they might protect against both seasonal and pandemic influenza strains. Here we discuss the humoral responses to influenza infection and vaccination, with particular reference to the pandemic H1N1 2009 virus and induction of broadly cross‐reactive stem‐binding antibodies. Having shown that cross‐reactive antibodies are preferentially induced by a pandemic hemagglutinin, the challenge is now to design a vaccine that applies these principles to the induction of heterosubtypic immunity.